Résultats De 5ans De Thyroïdectomie Au Service D’orl Et Chirurgie Cervico-Faciale De l’Hôpital National De Niamey (Niger) - S., Illé; L., James Didier; A., Saidou; N., Timi; R., Sani (European Scientific Journal, ESJ, 2017)
Purpose: To evaluate the results of thyroidectomy in the Oto-RhinoLaryngology and Neck Surgery office of the National Hospital of Niamey in Niger. Materials and methods: we analyzed the epidemiological aspects, the indications, the technics and the evolution of thyroidectomy through a retrospective and descriptive study conducted from January 2010 to December 2015. Results: Thyroidectomy represents 8, 51% (n = 236/2773) of the ENT operative activities and an average of 47.2 cases per year for 5 years. Among the patients, there were 15 men and 221 women, a sex ratio of 0.17. The mean age was 37.25 years (extreme 22 and 61 years). The operative indications are dominated by multinodular goiter euthyroid (43.22%), thyroid nodules (39.40%), hyperthyroidism (goiter and Basedow) and substernal goiters, respectively, representing 8.90% and 6.35%. The gestures performed were subtotal thyroidectomy in 56 cases (23.73%), complete thyroidectomy in 85 cases (36.02%) and lobo-isthmectomy in 95 cases (40.25%). The recurrent nerve was searched in 235 cases (99%) and found in 215 cases (91, 10%). It was found 1 case (0.42%) of splitting of the left nerve recurrent. 2 cases (0.84%) of immediate postoperative hemorrhage was recorded. Morbidity was 0.29% with 4 cases of definitive unilateral recurrent paralysis and 3 cases of transient hypoparathyroidism. No mortality was encountered. Conclusion: The thyroidectomy is a frequent intervention in the ENT and Neck Surgery office of the National Hospital of Niamey. Multinodular goiter remains the first surgical indication. Recurrent and hypoparathyroid morbidity was very low.